Dance Is More Than Meets the Eye—How Can Dance Performance Be Made Accessible for a Non-sighted Audience? - Bläsing, Bettina (Front Psychol, 2021)
Dance is regarded as visual art form by common arts and science perspectives. Definitions of dance as means of communication agree that its message is conveyed by the dancer/choreographer via the human body for the observer, leaving no doubt that dance is performed to be watched. Brain activation elicited by the visual perception of dance has also become a topic of interest in cognitive neuroscience, with regards to action observation in the context of learning, expertise and aesthetics. The view that the aesthetic experience of dance is primarily a visual one is still shared by many artists and cultural institutions, yet there is growing interest in making dance performances accessible for individuals with visual impairment / blindness. Means of supporting the non-visual experience of dance include verbal (audio description), auditive (choreographed body sounds, movement sonification), and haptic (touch tour) techniques, applied for different purposes by artists and researchers, with three main objectives: to strengthen the cultural participation of a non-sighted audience in the cultural and aesthetic experience of dance; to expand the scope of dance as an artistic research laboratory toward novel ways of perceiving what dance can convey; and to inspire new lines of (neuro-cognitive) research beyond watching dance. Reviewing literature from different disciplines and drawing on the personal experience of an inclusive performance of Simon Mayer's “Sons of Sissy,” we argue that a non-exclusively visual approach can be enriching and promising for all three perspectives and conclude by proposing hypotheses for multidisciplinary lines of research.